Measuring the Saudi Society's Awareness of Verbal Violence's Contribution to Low Self-Esteem, Feelings of Psychological Loneliness and Depression in Children - Barakati, Shahd Ibrahim Badr (Advances in Social Sciences Research Journal, 2022)
This study sought to measure the Saudi society's awareness of the impact of verbal violence on low self-esteem, feelings of psychological loneliness and depression among children , identify the forms of verbal and emotional violence practiced against the child, the effects resulting from the phenomenon of verbal violence against the child, measure the role of the media and the educational and counseling community institutions in reducing the phenomenon of verbal violence against the child, and determine the relationship of the number of family members, the level of parental education, and the social status to verbal violence against the child. The study released on the descriptive analytical approach, which depends on collecting data from the study sample using the questionnaire prepared for the purposes of this study, and studying and analyzing the sample responses. The study included a random sample of (88) fathers and mothers from the western, southern, central, northern and eastern regions of the Kingdom of Saudi Arabia. The researcher formulated a questionnaire of (23) items to measure Saudi society's awareness of the impact of verbal violence on low self-esteem, feelings of psychological loneliness and depression among adolescents. The questionnaire dealt with four topics as follows: 1. The first axis: the form of verbal and emotional violence against the child: (5) paragraph . 2. The second axis: knowledge of the effects resulting from the phenomenon of verbal violence against the child (8) paragraphs . 3. The third axis: the role of the media and the awareness and counseling community institutions in reducing the phenomenon of verbal violence against children (5) paragraphs . 4. The fourth axis: the relationship of the number of family members to verbal violence against the child (5) paragraphs. The study revealed the forms of verbal violence practiced against the child, and the results of the questionnaire showed an expressive percentage indicating the awareness of the respondents of the effects resulting from the phenomenon of verbal violence against the child and the presence of a relative need to Strengthen the role of the media and educational and counseling community institutions in reducing the phenomenon of verbal violence against the child. The results of the study also revealed a relationship between the increased number of family members and the prevalence of verbal violence against children. The study recommended, among a set of recommendations, to allocate television programs aimed at introducing the family.